The Impact of Commitment, Attitude, Subjective Norm and Perception of Behavioral Control on Intention to do Whistleblowing - Yasmin, Arifia; Noermansyah, Asrofi Langgeng (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
In institutions, the role of the whistleblower is often used to reduce the number of internal fraud that occurs, for example in goods procurement activities, asset embezzlement activities and other fraudulent activities. This research was to determine the consequence of commitment, attitude, subjective norms and perceived behavioral control on the intention to do whistle blowing in Harapan Bersama Polytechnic. This research is to make all of the information such as goods procurement to be more transparent. This research uses primary data sources obtained from distributing questionnaires to respondents, namely all employees of Harapan Bersama Polytechnic. The outcomes of this research are that there is an control of attitude variable on an intention to do the Whistle Blowing. For variable commitment, subjective norms and views of behavioral control have no effect on the aim to do the Whistle Blowing.